Terahertz response of patterned epitaxial graphene. (27th May 2015) - Sorger, Christian; Preu, Sascha; Schmidt, Johannes; Winnerl, Stephan; Bludov, Yuliy V; Peres, Nuno M R; Vasilevskiy, Mikhail I; Weber, Heiko B
Abstract: We study the interaction between polarized terahertz (THz) radiation and micro-structured large-area graphene in transmission geometry. In order to efficiently couple the radiation into the two-dimensional material, a lateral periodic patterning of a closed graphene sheet by intercalation doping into stripes is chosen. We observe unequal transmittance of the radiation polarized parallel and perpendicular to the stripes. The relative contrast, partly enhanced by Fabry–Perot oscillations reaches 20%. The effect even increases up to 50% when removing graphene stripes in analogy to a wire grid polarizer. The polarization dependence is analyzed in a large frequency range from <80 GHz to 3 THz, including the plasmon–polariton resonance. The results are in excellent agreement with theoretical calculations based on the electronic energy spectrum of graphene and the electrodynamics of the patterned structure.